A qualitative exploration of nursing undergraduates’ perceptions towards scaffolding in the flipped classroom of the Fundamental Nursing Practice Course: a qualitative study - Linghui Chen; Ting Lin; Siyue Tang (BMC Family Practice, 2021)
Abstract Background Although the benefits of using a flipped classroom in nursing education have been reported, there are few published studies attempting to understand students’ subjective experiences with scaffolding in a flipped classroom and the challenges they face as a result of this type of educational change. The purpose of this study was to describe students’ perspectives of scaffolding in the Flipped Classroom of the Fundamental Nursing Practice Course (FNPC-FC). Methods Thirty-four undergraduates were recruited and separated into four groups in the study. The data was collected through semi-structured focus group interviews. Thematic analysis was conducted to analyze the data in order to determine the themes in the interview transcriptions. Results The research revealed two primary themes with associated sub-themes: 1) challenging learning experience, and 2) teacher-student interaction. Conclusions Students will confront substantial challenges as scaffolding strategies are implemented in the flipped classroom. On the other hand, scaffolding in the flipped classroom can successfully train students to be self-directed learners and equip them with nursing skills when students are given appropriate support.